S69 Transcriptional Mechanisms Regulating Expression of the Avb6 Integrin in IPF. (19th November 2012) - Tatler, AL; Saini, G; Goodwin, A; Gbolohan, O; Clifford, RL; Al'Hourani, M; Porte, J; Violette, S; Weinreb, P; Knox, A; Laurent, G; Wolters, P; et al.
Abstract : TGF-β is fibrogenic cytokine implicated in the pathogenesis of idiopathic pulmonary fibrosis (IPF). The integrin αVβ6 can activate TGF-β, and dysregulation of this pathway is thought to play a role in the pathogenesis of pulmonary fibrosis. TGF-β induces αVβ6 integrin expression and aVb6 integrins are upregulated in fibrotic regions of lungs from patients with IPF. This raises the possibility that dysregulation of a self-regulating feedback loop may promote IPF. This study aims to investigate the mechanisms involved TGF-β-induced β6 expression and how this may be dysregulated in IPF. Using QPCR and flow cytometry we assessed expression of the integrin β6 (ITGB6) in lung epithelial cells. An ITGB6 promoter-luciferase construct and truncated mutants were used to identify the regulatory region of the promoter. Dominant negative (dn) constructs were used to assess the role of Smad proteins. Binding of transcription factors to the promoter was assessed by chromatin immunoprecipitation (ChIP). TGF-β caused concentration- and time-dependent increases in αVβ6 and ITGB6 mRNA, and increased activity of the ITGB6 promoter. Truncated mutants of the promoter showed that loss of 2 Smad binding sites resulted in loss of promoter activity. Co-transfection of dnSmad3 with the ITGB6 promoter reporter inhibited basal and TGF-β-induced promoter activity whereas dnSmad2 had little effect. dnSmad3 reduced TGF-β-induced αvβ6 cell surface expression. ChIP demonstrated binding of Smad3 and Smad4 to the promoter in response to TGF-β. Binding of Smad3 to the ITGB6 promoter was higher in lung tissue derived from IPF patients compared with controls. Finally, we identified a region of the ITGB6 promoter responsible for repressing transcription of the gene and demonstrate that siRNA targeting the transcription factor ELK1 increases αvβ6 expression. In conclusion, TGF-β increases expression of αVβ6 by transcriptional regulation involving Smad3. Furthermore, enhanced binding of Smad3 to the ITGB6 promoter in patients with IPF suggests dysregulated synthesis of αvβ6 integrins may promote IPF. Finally, we identified ELK1 as a potentially important negative regulator of αvβ6 expression. This highlights a positive feedback loop which could be dysregulated through hyperstimulation and impaired repression leading to amplification of αvβ6 mediated TGF-β activation that could be fundamental to IPF pathogenesis.